صناعة المعجم العربي الحديث - الواقع والتحديات- Modern Arab Lexicography-Reality and Challenges (مجلة إحالات, 2026)
إنّ الصناعة المعجمية أو المعاجمية كغيرها من الصّناعات تعدّ من أصعب وأعسر المسالك اللغوية، إذ يجب على صاحبها أن يكون مُلمّا بجُملة من الموادّ اللغوية والمعارف التاريخية، بالإضافة إلى جملة من الصّفات والتي تتمثل في الصّبر والتحمّل والجَلَدِ... الخ والتي يجب أن يتحلّى بها صانع المُعجم. وقد تطوّرت صناعة المعجم عالميًا من حيث الترتيب واختيار المداخل، وكيفية عرض المادّة وصارت لها تقنيات وأسس محدّدة من حيث الشكل والموضوع، ومع ذلك فمازال مُعجمنا العربي مشدُودًا إلى الماضي، ومازال معجميّونا حين يريدون وضع معجم حديث تشدُّهم تجربة العرب المُوغلة في القدم، ممّا جعل المعجم العربي الحديث يمرّ بأزمةٍ كبيرةٍ، فهُو غيرُ قادرٍ على مُواكبة الحداثةِ، وأغلب المعاجمِ الموجُودة اليوم لا تلبّي حاجة الأدباء والمثّقفين والنّاس عامّة، وبعيدة عن الاتجاهات الحديثة في صناعة المعجم ويُمكن وصفها بالمعاجم المهجُورة أو المُهملة؛ لأنّ مدى نجاحِها يتوقّفُ على مدى شيُوعِها واستعمالِها.lexicography is considered one of the most difficult linguistic pathways ,as the lexicographer must be familiar with a set of linguistic subjects and historical knowledge .in addition to a set of traits that the lexicographer must possess as for patience,endurance,determination...etc. Lexicography has evolved globally in terms of arrangement ,selection of entries and how to display the material.It has specific techniques and foundations in terms of form and subject matter.However,our Arabic Lexicon is still tight to the past ,and our Lexicons are still stick to theancient experience of Arabs when they attempt to develop a modern Lexicon.What made the modern Arab dictionary going through a major crisis which is its unablity to keep pace with modernity .So,most of the dictionaries that exist today do not meet the need of writers, intellectuals and people in general .They are away from modern trends in lexicography and can be described as abandoned or neglected dictionaries because the extent of its success goes back to its popularity and use.